STUDY SUBGRADE CHARACTERISTICS: DENSITY, WATER CONTENT AND CALIFORNIA BEARING RATIO - (NIM : 25008024); Pembimbing : Dr. Ir. Djunaedi Kosasih, MSc.; Dr. Ir. Eri Susanto Haryadi, ROCHAETI
Two important parameters in monitoring the results of basic soil compaction in the field, are density and moisture content. The level density is affected by moisture content, amount and type of compactor. In the field, the density is generally tested with sand cone; water content can be immediately known by using of speedy moisture tester, family of curve can be developed to facilitate the type of compactor in relation to the density level achieved. The quality of compaction is expressed in the CBR, was tested following the procedure according to AASHTO, the UK issued a test procedure and hereinafter referred to as BS, in Indonesia it is never used. Analysis of the results of testing the density of the soil type is not vulnerable to destruction, the value of dry density (γd) on water content (ω) is not influenced by certain compaction are made on the condition of remolded or unremolded specimens and repeated three; way A and B. Speedy moisture tester according to AASHTO, obtained the value of water content is below the value of oven dry water content, can be used in the field with sufficient specimens obtained correlation value curve of the oven dry moisture content. The results of analysis, these curves can be used such tools for conversion to oven dry moisture content on water content of the tests further. The result of cluster analysis is investigated with density curve Events remolded specimens according to standard density and density of the modified way B, in the field can be made by A on the variation of energy through the number of blows per layer 25x and 56x, and according to a modified density A on the number of blow 25x and 75x. Furthermore, to form a tighter clump curve, additional curves are made by following the slope of the curve that has been formed. CBR value according ASHTO and BS, is determined from a combination of test results and the modified standard compaction at 100% γdmak and ωopt; 98% γdmak on ω kering and ωbasah, soaked CBR at 100% γdmak and ωopt. The results of analysis obtained the same CBR value according to AASHTO and BS. The results of analysis, making samples, BS necessary testing to determine the number of blows in order to get the density to be reached while AASHTO number of blows have been determined. To get a CBR value, AASHTO needed 3 specimens and quite a BS.